2018
DOI: 10.3389/fnins.2018.00002
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metabolite Diffusion from Ultra-Short to Ultra-Long Time Scales: What Do We Learn, Where Should We Go?

Abstract: In vivo diffusion-weighted MR spectroscopy (DW-MRS) allows measuring diffusion properties of brain metabolites. Unlike water, most metabolites are confined within cells. Hence, their diffusion is expected to purely reflect intracellular properties, opening unique possibilities to use metabolites as specific probes to explore cellular organization and structure. However, interpretation and modeling of DW-MRS, and more generally of intracellular diffusion, remains difficult. In this perspective paper, we will fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 38 publications
6
32
0
Order By: Relevance
“…2). Taking all b-values into account for ADC estimation then yielded a more than 4-fold averaged ADC value for NAA, tCr and tCho (for the cohort data) when moving from long TD (PGSE) to short TD (OGSE), which is clearly much larger than expected from theory and animal data (Najac et al, 2016) (Valette et al, 2018). However, scrutinizing the signal decay for OGSE, one will realize that the area decay is not truly Fig.…”
Section: In Vivo Application In Human Parieto-occipital Cortexmentioning
confidence: 92%
See 2 more Smart Citations
“…2). Taking all b-values into account for ADC estimation then yielded a more than 4-fold averaged ADC value for NAA, tCr and tCho (for the cohort data) when moving from long TD (PGSE) to short TD (OGSE), which is clearly much larger than expected from theory and animal data (Najac et al, 2016) (Valette et al, 2018). However, scrutinizing the signal decay for OGSE, one will realize that the area decay is not truly Fig.…”
Section: In Vivo Application In Human Parieto-occipital Cortexmentioning
confidence: 92%
“…Diffusion-weighted magnetic resonance spectroscopy (DW-MRS 1 Depending on diffusion time (TD), apparent diffusion coefficients (ADCs) are affected by different dimensions and mechanisms of cellular barriers (Valette et al, 2018). Pulsed gradient spin-echo (PGSE) sequences, commonly used, measure at long TD (>50 ms) where ADCs represent diffusion mostly along tissue fibers (Kroenke et al, 2004) (Najac et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the complexity of metabolic dynamics in the intra-cellular environment, previous studies have shown evidence that the metabolites under investigation mainly diffuse in the cellular cytoplasm, with a negligible fraction confined in sub-cellular compartments. 26,[34][35][36][37] Thus, the metabolite displacement probed by DW-MRS mostly reflects the microstructure of the cells in which metabolites are compartmentalized. Under our experimental conditions (eg maximum b = 6 ms/μm 2 , t d = 64 ms), it was not possible to extract from the DW-MRS data quantitative morphological parameters such as soma radii, fiber diameters and length; however, variations in metabolite diffusion allowed us to capture qualitative alterations in cell size.…”
Section: Mins and Tcho Diffusion Probe Ongoing Inflammation Processmentioning
confidence: 99%
“…From metabolite diffusion measures, it is possible to derive information on cell size and morphology, [5][6][7][8] as well as on the properties of the intracellular environment, such as viscosity and molecular crowding. 9 When combined with DW imaging techniques, DW-MRS provides a unique way to differentiate between axonal degeneration, glial activation, and demyelination. [10][11][12][13] Although very promising, the application of DW-MRS techniques in clinical studies is challenging due to the intrinsic low signal-to-noise ratio (SNR) of metabolites, especially when the spectra are acquired at high diffusion-weightings.…”
Section: Introductionmentioning
confidence: 99%